Guardian Of Gambut: Media Digital Interaktif Berbasis Etnosains Lahan Gambut untuk Meningkatkan Berpikir Kritis, Literasi Sains, dan Sikap Peduli Lingkungan - Mohamad Nor Aufa; Gusti Nida Nurkhaliza; Chandra Anugrah Putra; Muqor Rama Hasanah; Muhammad Hasbie; Rahmadi; Hendra (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aimed to develop and examine the effectiveness of an ethnoscience-based interactive digital media on peatland issues entitled Guardian of Gambut for the topic of Ecosystems and Biodiversity in junior high school. The study was motivated by students’ low critical thinking skills and scientific literacy, as well as their limited environmental awareness due to science instruction that remains focused on memorization and lacks contextualization to local ecological issues. The research employed a Research and Development (R&D) approach using the ADDIE model, followed by a quasi-experimental pretest–posttest control group design. The participants were students of class VIIB as the control group and VIIC as the experimental group at SMP Muhammadiyah Palangka Raya. The findings indicate that the developed media was categorized as very valid and highly practical, and proven effective in improving students’ critical thinking skills, scientific literacy, and environmental care attitudes. The experimental group demonstrated higher improvement than the control group, with significant differences and a large effect size. In conclusion, the Guardian of Gambut interactive digital media is valid, practical, and effective in enhancing students’ cognitive and affective competencies through contextual ethnoscience-based science learning. Keywords: Critical Thinking, Environmental Care Attitude, Interactive Digital Media, Peatland Ethnoscience, Scientific Literacy